Macca tree manns - Palmer, Addeah (Kingston : Ian Randle Publishers, 2015)
The Manns family returned home to Macca Tree without much fanfare in the middle of the night, taking up residence in a dilapidated shack no decent member of the Westmoreland community would dare enter. When the community members realised they had returned, they were surprised and upset that the Manns would ever set foot in Macca Tree again after what they had done. But Gloria Mann, the overbearing, money-hungry, foul-mouthed matriarch of the family would not let the disapproving chatter of the community force her to leave. She and her emasculated husband, Kenneth, and their three neglected children stayed to the dismay of the community who bore the brunt of the Manns' quarrels, Gloria's outbursts and their unruly children's mischief. In hopes of rebuilding her home to its former glory and silencing naysayers who believed the Manns to be the worst of the community, Gloria schemes with her cousin, Monica, to start a savings plan within the local church, but it all goes wrong. Macca Tree Manns is a Jamaican novel masterfully injected with humour, authenticity and vivid imagery, and marks Addeah Palmer's first venture into mainstream writing.
NLJCols20082021
Keywords: Homecoming -- Jamaica -- Fiction; Interpersonal relations -- Jamaica -- Fiction; Families -- Jamaica -- Fiction; Communities -- Jamaica -- Fiction; Communities; Families; Homecoming; Interpersonal relations; Jamaica; Fiction; Jamaican fiction -- 21st century